Development of Live Attenuated Salmonella Typhimurium Vaccine Strain Using Radiation Mutation Enhancement Technology (R-MET) - Ji, Hyun Jung; Jang, A-Yeung; Song, Joon Young; Ahn, Ki Bum; Han, Seung Hyun; Bang, Seok Jin; Jung, Ho Kyoung; Hur, Jin; Seo, Ho Seong (Frontiers in Immunology, 2022)
Salmonella enterica is a leading cause of food-borne diseases in humans worldwide, resulting in severe morbidity and mortality. They are carried asymptomatically in the intestine or gallbladder of livestock, and are transmitted predominantly from animals to human via the fecal-oral route. Thus, the best preventive strategy is to preemptively prevent transmission to humans by vaccinating livestock. Live attenuated vaccines have been mostly favored because they elicit both cellular and humoral immunity and provide long-term protective immunity. However, developing these vaccines is a laborious and time-consuming process. Therefore, most live attenuated vaccines have been mainly used for phenotypic screening using the auxotrophic replica plate method, and new types of vaccines have not been sufficiently explored. In this study, we used Radiation-Mutation Enhancement Technology (R-MET) to introduce a wide variety of mutations and attenuate the virulence of Salmonella spp. to develop live vaccine strains. The Salmonella typhimurium, ST454 strain was irradiated with a high-dose Cobalt60 gamma-irradiator for 1 h to maximize the mutation rate, and attenuated daughter colonies were screened using in vitro macrophage replication capacity and in vivo mouse infection assays. Among 30 candidates, ATOMSal-L6, with 9,961-fold lower virulence than the parent strain (ST454) in the mouse LD50 model, was chosen. This vaccine candidate was mutated at 71 sites, and in particular, lost one bacteriophage. As a vaccine, ATOMSal-L6 induced a Salmonella-specific IgG response to provide effective protective immunity upon intramuscular vaccination of mice. Furthermore, when mice and sows were orally immunized with ATOMSal-L6, we found a strong protective immune response, including multifunctional cellular immunity. These results indicate that ATOMSal-L6 is the first live vaccine candidate to be developed using R-MET, to the best of our knowledge. R-MET can be used as a fast and effective live vaccine development technology that can be used to develop vaccine strains against emerging or serotype-shifting pathogens.